Penentuan Nilai FICI Kombinasi Ekstrak Etanol Kulit Daun Lidah Buaya (Aloe vera (L) Burm.f) dan Gentamisin Sulfat Terhadap Bakteri Escherichia coli - A’lana, Lu’lu’; Sari, Rafika; Apridamayanti, Pratiwi (UI Scholars Hub, 2017)
The combined use of natural materials and antibiotic compound is one of treatment that can be done against infections caused by bacteria. This combination is expected to be more potent to inhibit the bacteria with lower side effects. FICI (Fractional Inhibitory Concentration Index) is an index that can indicate the activity of a combination of natural ingredients and antibiotic compounds. FICI would indicate that the combination has a synergistic effect, additive, indifferent or antagonistic. The aim of this study is to determine the FICI to the combination of Aloe vera leaves skin (Aloe vera (L.) Burm.f.) ethanol extract and gentamicin sulphate againts Escherichia coli. FICI was determined by disc diffusion method. Combination of Aloe vera leaves skin (Aloe vera(L.) Burm.f.) ethanol extract and gentamicin sulphate with concentration of 1.25 mg/mL + 2,5 µg/mL was not form zone of inhibition; while the concentration of 2.5 mg/ml + 5 µg/ mL formed zone of inhibition of 6.95 mm; 6.75 mm; and 6.65 mm. The results showed that the combination of Aloe vera leaves skin (Aloe vera (L.) Burm.f.) ethanol extract and gentamicin sulphate against the Escherichia coli has the indifference effect on Escherichia coli, and FICI to this combination is 2.